A Look to the Biogas Generation from Organic Wastes in Colombia - Contreras, Michel DurÃ¡n; Barros, Rodrigo Sequeda; Zapata, Jorlany; Chamorro, Marley Vanegas; Arrieta, Alberto Albis (International Journal of Energy Economics and Policy, 2020)
In line with the goals of the Paris Agreement and the guidelines of Conpes 3874 of 2016, Colombia has adopted different strategies to optimize the use of biomass as an energy source and the management of materials in urban centers, establishing short and long term goals that convene actors towards the innovation of traditional models to turn them into circulars, proposing promotion mechanisms to be developed as enablers of the circular economy, among which is the production of biogas from different economic sectors. This document shows the current situation of biogas in Colombia, its participation in the national electricity sector, as well as the existing potential for its application and diversification of the existing energy matrix. Keywords: Environmental pollution, Energy policy, Alternative fuels, Biogas, Renewable Energy, Anaerobic digestion. JEL Classifications: Q16, Q42, Q47, Q48. DOI: https://doi.org/10.32479/ijeep.9639